Psychological aspects and the roles for student’s sport performance - Masrun; Alnedral; Yendrizal (UIR Press, 2022)
Sports achievement is influenced by various factors such as; physical, technical, tactical and psychological factor. The purpose of this study is to see the relation of self-efficacy factors, achievement motivation, and its relation to self-confidence and its effect on sports performance. This research was conducted on 87 students. This is quantatif research and using path analysis method. The sample was taken by technique purposive random samplin and the sample was 45 people with certain considerations. The data of self-efficacy, achievement motivation, and self-confidence was taken by using valid and reliable quistionnaire, and the sport performance data taken from the performance (medal) are already gotten. For testing the structural effects of the model from this study, researchers used IBM SPSS software. The results show that self efficacy, achievement. motivation, and self-confidence have a significant influence on the athletes' sports performance inndividual sports both of directly and indirectly, or totally. The implications of the theory obtained reinforce that the variables tested have a direct impact toward athletes achievement of the Student Sport Training Center in West Sumatera Province. The limitation of this study is the instrument that needs to be developed more accurately and comprehensively to reveal psychological conditions.